Economic Prospects and Policy Challenges for the GCC Countries : 2021 (Arabic Executive Summary). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2021)
GCC policymakers moved quickly to mitigate the health and economic impacts of twin COVID-19 and oil price shocks. Infection rates have declined across the GCC to well below previous peaks, though countries have experienced successive waves of the virus, and economic recoveries have begun to take hold. Nevertheless, GCC policymakers must navigate a challenging and uncertain landscape. The pandemic continues to cloud the global outlook as countries are in different phases of recovery, with varied growth prospects and policy space.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Monetary Policy; Political Economy